Influence of Surface Corona Discharge Process on Functional and Antioxidant Properties of Bio-Active Coating Applied onto PLA Films - Ana Božović; Katarina Tomašević; Nasreddine Benbettaieb; Frédéric Debeaufort (MDPI AG, 2023)
PLA (polylactic acid) is one of the three major biopolymers available on the market for food packaging, which is both bio-based and biodegradable. However, its performance as a barrier to gases remains too weak to be used for most types of food, particularly oxygen-sensitive foods. A surface treatment, such as coating, is a potential route for improving the barrier properties and/or providing bioactive properties such as antioxidants. Gelatin-based coating is a biodegradable and food-contact-friendly solution for improving PLA properties. The initial adhesion of gelatin to the film is successful, both over time and during production, however, the coating often delaminates. Corona processing (cold air plasma) is a new tool that requires low energy and no solvents or chemicals. It has been recently applied to the food industry to modify surface properties and has the potential to significantly improve gelatin crosslinking. The effect of this process on the functional properties of the coating, and the integrity of the incorporated active compounds were investigated. Two coatings have been studied, a control fish gelatin-glycerol, and an active one containing gallic acid (GA) as a natural antioxidant. Three powers of the corona process were applied on wet coatings. In the test conditions, there were no improvements in the gelatin crosslinking, but the corona did not cause any structural changes. However, when the corona and gallic acid were combined, the oxygen permeability was significantly reduced, while free radical scavenging, reduction, and chelating properties remained unaffected or slightly improved.